2022
DOI: 10.1007/s12665-022-10277-0
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative risk assessment in El-Jadida (Northern Atlantic Coast of Morocco) for a tsunami scenario equivalent to that of the 1755 Lisbon earthquake

Abstract: HAL is a multi-disciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
1
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 68 publications
1
1
2
Order By: Relevance
“…In Casablanca the MXH calculated is 5.5 m which is smaller than the value of 10 m found by [13]. This difference is probably related to the GB fault parameters used in [13] which correspond to those in the work of [1], whereas in our study we used the new GBF fault parameters used in [8]. Concerning Rabat, the MWH recorded is almost 1 m less than the value recorded in Casablanca.…”
Section: Discussioncontrasting
confidence: 71%
See 2 more Smart Citations
“…In Casablanca the MXH calculated is 5.5 m which is smaller than the value of 10 m found by [13]. This difference is probably related to the GB fault parameters used in [13] which correspond to those in the work of [1], whereas in our study we used the new GBF fault parameters used in [8]. Concerning Rabat, the MWH recorded is almost 1 m less than the value recorded in Casablanca.…”
Section: Discussioncontrasting
confidence: 71%
“…Furthermore, the magnitude obtainned for the invistigated scenario is about 8.5, which is smaller than the magnetudes calculated in [14] (8.75 -9) as well as those calculated by [15], [1] and [16]. However, recent estimates of the magnitude of the 1755 event have a range of 7.2 -8.2, which is more similar to the results obtained by [13]. However, our belief is that the difference will not be significant enough to radically alter the results for future tsunami risks in Morocco.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Furthermore, extreme events scenarios have not been investigated for the north of Morocco. Only the famous 1755 event, supposedly being the most destructive one in the Atlantic region, has been extensively studied (Amine et al, 2018a;Baptista et al, 2003;El Moussaoui et al, 2017;Omira et al, 2012;Ramalho et al, 2018;Tadibaght et al, 2022a). Overall, the 1755 Atlantic case prevalence and the lack of research on submarine landslide tsunamis are two reasons that justify the significant need to fill knowledge gaps on the exposure of the northern coast of Morocco to tsunami.…”
Section: Scientific Backgroundmentioning
confidence: 99%
“…Knowing that one of the disasters that threatens the city is mainly flooding, especially since the city is surrounded by two rivers, for example, the river Oued El Maleh, which causes floods that cause significant losses; what increases the risk is its impact on the largest petroleum region in Morocco, as was witnessed in 2002 [3]. Another significant risk is that the city's coast is vulnerable to tsunamis, as studies have confirmed that the city has already been hit by a tsunami in previous centuries, reaching a height of 8 meters [4].…”
Section: Introductionmentioning
confidence: 99%